PERKUATAN DINDING PENAHAN TANAH EKSISTING SETINGGI 8 -1000mm YANG MEMBAHAYAKAN MASYARAKAT DI RANGKASBITUNG - Susilo, Alfred Jonathan; Prihatiningsih, Aniek; Ongga, Fernando Putra; Tarigan, Kezia Demelia Khovi Br (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
ABSTRACT The team observed the condition of the walls, gathered information from building owners, combined the received information and finally conducted an engineering analysis. Based on this study, the best recommendation was obtained for the building owner to make an additional strengthening structure in the form of a combination of reinforced concrete column and beam with a cross section size of 300 x 300mm. The strengthening structure installed in the form of right triangles as high as the retaining wall. The strengthening structure located 1500mm apart. The strengthening column and beam are supported by two 300mm diameter drilled pile foundations tied together by 1500 x 300 x 300mm pile caps. The drilled pile foundation is buried to a depth of 600mm lying on above hard layer soil. Between strengthening structures that are 1500mm apart are tied with reinforced concrete beam with a 300 x 300mm cross section to unite the strengthening structure. In conducting this study of solving the continuing damage of retaining wall the lecturers and students discussed to find the most appropriate study for the solution to the existing retaining walls. Detailed calculations and drawings are carried out by students and lecturers giving suggestions and directions until conclusions are obtained and recommendations are made to building owners. Recommendations were submitted to the building owner and then implemented the Team's recommendations by constructing the strengthening structure, until finally the strengthening structures had been installed on the 8000 and 10000mm high retaining walls.